2016
DOI: 10.1530/eje-15-0674
|View full text |Cite
|
Sign up to set email alerts
|

Reduced β-cell function in early preclinical type 1 diabetes

Abstract: ObjectiveWe aimed to characterize insulin responses to i.v. glucose during the preclinical period of type 1 diabetes starting from the emergence of islet autoimmunity.Design and methodsA large population-based cohort of children with HLA-conferred susceptibility to type 1 diabetes was observed from birth. During regular follow-up visits islet autoantibodies were analysed. We compared markers of glucose metabolism in sequential intravenous glucose tolerance tests between 210 children who were positive for multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 35 publications
(28 reference statements)
2
43
0
Order By: Relevance
“…We previously reported that β cells start losing the capability to secrete insulin before signs of inflammatory cell infiltration or conspicuous cytokine expression emerged in [8], and this notion was supported by such observations in a recent clinical report [9]. We also observed that a lack of zinc results in a significant decline of insulin secretion in conjunction with decreased ZIP8 ( Z rt- and i rt-like p rotein 8, a zinc uptake transporter) expression in Sprague-Dawley rats [10].…”
Section: Introductionsupporting
confidence: 53%
“…We previously reported that β cells start losing the capability to secrete insulin before signs of inflammatory cell infiltration or conspicuous cytokine expression emerged in [8], and this notion was supported by such observations in a recent clinical report [9]. We also observed that a lack of zinc results in a significant decline of insulin secretion in conjunction with decreased ZIP8 ( Z rt- and i rt-like p rotein 8, a zinc uptake transporter) expression in Sprague-Dawley rats [10].…”
Section: Introductionsupporting
confidence: 53%
“…When insulin resistance was estimated in our study, we indeed observed a significant increase over the follow‐up in progressors but not in non‐progressors, and the groups differed significantly at the 12‐month visit. In the DIPP study, there was no difference in insulin resistance between progressors and non‐progressors, but a significant increase was observed in the last 2 samples before diagnosis . As insulin sensitivity decreases during puberty and is associated with a compensatory increase in insulin secretion, it is difficult to determine whether the increased insulin secretion in the progressors is the result of such a compensatory mechanism, or if it is related to the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…In the DPT‐1 study, it was shown that decreased C‐peptide response to oral glucose occurs at least 2 years before the diagnosis of T1D in islet cell autoantibody‐positive first‐degree relatives <15 years of age, and maintained stimulated C‐peptide levels actually seem related to non‐progression to clinical disease among risk‐individuals . Recent results from the DIPP study showed decreased first phase insulin response in high‐risk individuals as long as 4 to 6 years prior to disease onset . For fasting C‐peptide however, there is less evidence for substantial changes before clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reduced insulin resistance as the infection resolves may provide a plausible explanation for the remission period occurring shortly after clinical onset in the majority of people (Figure ) as well as for reports of self‐resolving T1D and fluctuating symptoms of T1D several months before T1D diagnosis . In people progressing to T1D, insulin release in response to oral glucose remains normal until about 1 to 5 years before diagnosis, then glucose metabolism starts to deteriorate . These clinical observations lead to the formulation of a model for the development of T1D in which a relative lack of insulin secretory capacity develops as a consequence of increasing demands, rather than a major loss of β‐cell mass.…”
Section: Total β‐Cell Volume Governs Who Will Be Affected By T1dmentioning
confidence: 99%